MODEL PROBLEM BASED LEARNING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI KELAS V SDN 05 PADANG PASIR - Imam Taufiq; Elfia Sukma; Tri Susila Wati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research is motivated by the mathematics learning outcomes of student of grade V at SDN 05 Padang Pasir, Padang City is still low score. This is due to the state of the covid pandemic that hit Indonesia and has not used a learning model that is in accordance with the characteristics of students. The purpose of this research was to describe the application of the Problem Based Learning (PBL) learning model to improve learning outcomes in grade V at SDN 05 Padang Pasir, Padang City. This type of research is Classroom Action Research using qualitative and quantitative approaches. Research procedures are planning, implementation, observation, and reflection. Research data in the form of observations and actions as well as test results. The data source is the process and results of the implementation of learning by using the PBL model on data processing. This research was conducted in Semester II of the 2020/2021. The research subjects are teacher as observer, researcher as practice, and class V students as many as 25 people. The results showed an increase in the average learning outcomes of students in the first cycle from 68.95 to 87.8 in the second cycle. The results of the RPP observations in the first cycle from 88.9% to 100% in the second cycle. The results of observations of teacher and student aspects in the first cycle were 75% to 100% in the second cycle. It can be said that the PBL model can improve the mathematics learning outcomes of data processing materials in class V SDN 05 Padang Pasir, Padang City